Prognostic Value Of The Preoperative Neutrophil To Lymphocyte Ratio In Patients With Sinonasal Squamous Cell Carcinoma - Zhong, Bing (Cancer Manag Res, 2019)
OBJECTIVE: This study explored the effectiveness of a new inflammatory prognostic system, using preoperative neutrophil to lymphocyte ratio (NLR) to predict the postoperative survival rate of patients with sinonasal squamous cell carcinoma (SSCC). METHODS: Patients diagnosed with SSCC who undergone surgically treated without neoadjuvant therapy were included in the study between May 2008 and October 2017. Preoperative NLR is defined as: preoperative neutrophil/postoperative lymphocyte ratio. The prognostic value was uncovered by univariate and multivariate Cox hazards analysis. RESULTS: A total of 147 patients were included in this study. Through the multivariate analysis, pathological T stage (hazard ratio [HR] 1.719, confidence interval [CI] 1.277–3.642, p<0.001), pathological N stage (HR 1.344, 95% CI 1.015–2.776, p<0.001), and preoperative NLR (HR 1.579, 95% CI 1.217–3.092, p=0.002) were independent risk factor for overall survival (OS). Pathological T stage (HR 1.835, 95% CI 1.141–3.132, <0.001), pathological N stage (HR 1.281, 95% CI 1.169–2.476, p<0.001), and preoperative NLR (HR 1.688, 95% CI 1.162–3.363, p p<0.001) were also independently associated with disease-free survival (DFS). Pathological T stage (HR p<0.001, 95% CI 1.537–3.021, p<0.001), pathological N stage (HR1.571, 95% CI 1.157–2.258, p<0.001), and preoperative NLR (HR 1.509, 95% CI 1.153–3.104, p=0.001) were independent risk factors for disease-specific survival (DSS). CONCLUSION: The preoperative NLR is considered to be a useful predictor of postoperative survival in SSCC patients.